Caracterização da resposta imune humoral em trabalhadores da área da saúde frente a antígenos recombinantes de Mycobacterium tuberculosis - REIS, Michelle Cristina Guerreiro dos (2007)
Tuberculosis (TB), one of the oldest disease in the world, is until our days a public health concern. It s believed that one third of the world s population is latently infected. Brazil is an endemic area for TB and its incidence in 2005 was about 60 cases per 100.000 inhabitants. One of the most important challenge in TB control is the identification of individuals who are latent infected. Health Care Workers (HCW) are at high risk of getting infected with Mycobacterium tuberculosis and because of that they had increased chances to became ill. The aim of this work was to elucidate the sorological profile of latent infected HCW through the antibody response against proteic recombinant antigens from Mycobacterium tuberculosis, GLcB, Hspx and MPT51. It was observed that almost 70% of HCW presented antibodies (IgM and IgG) against these antigens. When IgM was measured, the negative TST HCW showed higher antibodies s levels than the positive TST HCW. When IgG was measured, negative and positive TST HCW showed similar antibodies´s levels. Men and women also showed similar antibodies´s levels against those antigens. The antibodies s levels were also similar between BCG-vaccinated and BCG non-vaccinated HCW, the same occurs among the different professional categories. There isn t any relation between the antibody responses (humoral response) and TST results (cellular response). These results showed that the majority of the HCW presented antibodies against the proteic recombinant antigens GLcB, Hspx e MPT51 of Mycobacterium tuberculosis independent of the TST response.